Dose-Response Relationship of Uric Acid With Fasting Glucose, Insulin, and Insulin Resistance in a United States Cohort of 5,148 Non-diabetic People - Han, Yingdong; Han, Xinxin; Yin, Yue; Cao, Yu; Di, Hong; Wu, Juan; Zhang, Yun; Zeng, Xuejun (Frontiers in Medicine, 2022)
Background: There is a limited number of studies on the dose-response relationship between serum uric acid and impaired glucose metabolism in people without diabetes, and no large-scale research exploring the relationship in women without diabetes based on menopausal status. Consequently, the present study aimed to investigate the above relationship in U.S. adults without diabetes. Method: Data from 2498 men and 2650 women aged ≥ 20 years were obtained from the National Health and Nutrition Examination Survey 2011-2016 conducted in the U.S.A. Binary logistic regression analysis was applied to evaluate the association between uric acid and impaired glucose metabolism. Restricted cubic spline analysis, sensitivity analysis, and stratified analysis by menopausal status were performed to explore the above relationships. Results: A positive correlation was found between uric acid and the risk of insulin resistance in all participants (P <0.05). In binary logistic regression analysis, after adjusting for confounding factors, compared with the lowest quartile of uric acid, the odds ratio (95% confidence intervals) of insulin resistance in the highest quartile was 1.9 (1.1-3.1) and 2.2 (1.2-4.3) in men and women, respectively. A significant positive relationship was also observed between uric acid and impaired fasting glucose and hyperinsulinemia in women, while in men, uric acid was positively associated with the risk of hyperinsulinemia but not impaired fasting glucose. Restricted cubic spline showed that the odds ratios of insulin resistance and hyperinsulinemia increased with elevating uric acid levels in both men and women. When stratified by menopause, the association remained significant in pre-menopausal women aged ≥ 20, but insignificant in post-menopausal women. Conclusions: Uric acid was positively associated with the risk of impaired glucose metabolism in a cohort of U.S. adults, and uric acid increased the risk of insulin resistance in pre-menopausal, but not in post-menopausal women.